Hubungan antara Pengetahuan dan Perilaku Masyarakat Kecamatan Biatan Kabupaten Berau terhadap Penggunaan dan Resistensi Obat Antibiotik: The Relationship between Knowledge and Behavior of the People of Biatan District, Berau Regency on the Use and Resistance of Antibiotic Drugs - Vina Mardiyanti Aprilia; Nur Mita; Adam M. Ramadhan; Riski Sulistiarini (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Antibiotics are drugs used to treat infections. Infection is a disease problem that often occurs in developing countries in Indonesia. The purpose of this study was to determine the level of knowledge and behavior of the community in the use of antibiotics and the relationship between knowledge and behavior in the use of antibiotic drugs in the people of Tanjung Redeb District, Berau Regency. This research was conducted by distributing questionnaires to 119 respondents using a cross sectional method with purposive sampling of respondents. The results showed that the level of knowledge of the people of Berau Regency was quite good, namely 47.89% and the results of research based on community behavior were well-behaved with a percentage of 42.01%. The results of the Spearman correlation analysis show that there is a relationship between the level of knowledge on behavior with a correlation coefficient of 0.258, so the relationship between variables is low.